SEX, GENDER, SOCIETY - Petrov, Александър (E-Journal VFU, 2025)
The text outlines the boundaries of gender-related concepts from a biological and psychological point of view. Account is also taken of the socio-political aspects of speech and the cultural framework of gender-related actions. The anatomical-physiological determinants of gender are considered in their relation to the processes of identification, as part of the mental structuring (in the sense of the analytical paradigm), the "I-image", identity and social roles related to gender. Two biologically determined sex and their inclusion in the concept of "Me". The body, who is considered as "the other", as this, who exist before "Me", and which implies psychic work to achieve integrity. Or not.
Keywords: body; identification; identity; role